THE RELATIONSHIP BETWEEN WORK ENGAGEMENT AND ORGANIZATIONAL COMMITMENT IN EMPLOYEES BLUD NORTH KONAWE HOSPITAL IN 2026 - Fendry Pratama; Lisnawati Lisnawati; Noviani Munsir (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Work engagement is an important factor that can influence employees’ attachment and commitment to an organization. Employees who demonstrate enthusiasm, dedication, and full involvement in their work tend to have a stronger sense of loyalty and attachment to the organization. This study aimed to determine the relationship between work engagement and organizational commitment among employees at the BLUD Konawe Utara Hospital in 2026. This research employed a quantitative method with a cross-sectional design. The study sample consisted of 59 respondents selected using a simple random sampling technique. Data were collected using a work engagement questionnaire covering the dimensions of vigor, dedication, and absorption, as well as an organizational commitment questionnaire. Data analysis was conducted using univariate and bivariate analyses with the Chi-Square test at a significance level of α = 0.05. The results showed that most respondents had a good level of work engagement, with 42 respondents (71.2%), while 17 respondents (28.8%) had a poor level of work engagement. Organizational commitment was also predominantly categorized as good, with 37 respondents (62.7%), while 22 respondents (37.3%) were categorized as having poor organizational commitment. The Pearson Chi-Square test results showed a value of χ² = 14.199 with a significance value of p = 0.000 (p < 0.05), indicating a significant relationship between work engagement and organizational commitment among employees at the BLUD Konawe Utara Hospital. It can be concluded that the better the employees’ work engagement, the higher their organizational commitment. Therefore, hospital management should improve employee engagement through supportive leadership, fair rewards, competency development, and the creation of a conducive work environment to strengthen employees’ organizational commitment. Work engagement merupakan salah satu faktor penting yang dapat memengaruhi keterikatan dan komitmen karyawan terhadap organisasi. Karyawan yang memiliki semangat, dedikasi, dan keterlibatan penuh dalam pekerjaannya cenderung memiliki rasa loyalitas dan keterikatan yang lebih kuat terhadap organisasi. Penelitian ini bertujuan untuk mengetahui hubungan work engagement terhadap organizational commitment pada karyawan BLUD Rumah Sakit Konawe Utara Tahun 2026. Penelitian ini menggunakan metode kuantitatif dengan desain cross-sectional. Populasi dalam penelitian ini adalah karyawan BLUD Rumah Sakit Konawe Utara, dengan jumlah sampel sebanyak 59 responden yang dipilih menggunakan teknik simple random sampling. Pengumpulan data dilakukan menggunakan kuesioner work engagement yang meliputi dimensi vigor, dedication, dan absorption serta organizational commitment. Analisis data dilakukan secara univariat dan bivariat menggunakan uji Chi-Square dengan tingkat kemaknaan α = 0,05. Hasil penelitian menunjukkan bahwa sebagian besar responden memiliki work engagement dalam kategori baik sebanyak 42 responden (71,2%), sedangkan 17 responden (28,8%) berada dalam kategori kurang. Organizational commitment sebagian besar berada dalam kategori baik, yaitu sebanyak 37 responden (62,7%), sedangkan 22 responden (37,3%) berada dalam kategori kurang. Hasil uji Pearson Chi-Square menunjukkan nilai χ² = 14,199 dengan nilai signifikansi p = 0,000 (p < 0,05), sehingga terdapat hubungan yang signifikan antara work engagement dengan organizational commitment pada karyawan BLUD Rumah Sakit Konawe Utara. Disimpulkan bahwa semakin baik work engagement karyawan, maka semakin tinggi pula organizational commitment yang dimiliki. Oleh karena itu, manajemen rumah sakit perlu meningkatkan keterlibatan kerja melalui kepemimpinan yang suportif, pemberian penghargaan yang adil, pengembangan kompetensi, serta penciptaan lingkungan kerja yang kondusif guna memperkuat komitmen organisasi karyawan.